Functionalized epigallocatechin gallate copolymer inhibit dentin matrices degradation: Mechanical, solubilized telopeptide and proteomic assays - Prakki, Anuradha; Xiong, Yaoyang; Bortolatto, Janaina; Goncalues, Lucelia Lemes [UNESP]; Bafail, Arwa; Anderson, Greg; Stauroullalzis, Alexander Terry (Elsevier B.V., 2018)
Objectives. We investigated the biostability of dentin organic matrices treated with epigallocatechin gallate (EGCG) in comparison to chlorhexidine (CHX), both extracted from functionalized copolymers. Methods. Copolymers were prepared with bis-GMA:TEGDMA and incorporated with 1% of EGCG or CHX (w/w). Blank copolymers were used as control. Copolymer samples were individually stored in 1 mL deionized water to produce copolymer extracts. Dentin matrices were obtained by demineralization of dentin disks in 10% phosphoric acid solution. Matrices were individually treated with 1 mL of the copolymer extracts or distilled water for 48 h. Collected extracts were analyzed by high-performance liquid chromatography (HPLC) for the presence and quantification of EGCG, CHX, and copolymer by-products. Treated dentin matrices were tested for ultimate tensile strength, gravimetric changes, and swelling ratio. The treatment media were tested for total protein concentration, and dentin protease activity through solubilized telopeptide (ICTP- and CTX-ELISA) assays. The treatment media were also submitted to proteomic analysis. Results. HPLC identified released unreacted copolymer species and showed higher release of CHX compared to EGCG from respective copolymer extracts. EGCG extract inhibited activity of dentin proteolytic enzymes and promoted collagen biomodification observed by the telopeptide assays and in the changes to dentin matrix properties. The proteomic results showed less collagenous peptide hits in the EGCG extract media compared to CHX, and suggest compound-specific dentin protein binding interactions. Significance. This study demonstrates specific antiproteolytic effect and protein interactions of EGCG copolymer extract directly on dentin. This represents an advancement in dental materials which can impact the clinical procedures. (C) 2018 The Academy of Dental Materials. Published by Elsevier Inc. All rights reserved.
Keywords: EGCG; Proteomics; Dentin; Bis-GMA; HPLC; TEGDMA